Girl reading - Ward, Katie (London : Virago Press, 2012)
"An orphan poses nervously for Renaissance maestro in medieval Siena, and an artist's servant girl in seventeenth-century Amsterdam snatches a moment away from her work to lose herself in tales of knights and battles. In a Victorian photography studio, a woman holds a book that she barely acknowledges while she waits for the exposure, and in a Shoreditch bar in 2008 a woman reading catches the eye of a young man who takes her picture."--Cover
Keywords: Portraits -- Fiction; Fiction